2021
DOI: 10.1021/acsnano.0c10775
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Imaging of Competition between Surface Diffusion and Phase Transition during the Intermetallic Formation of Faceted Particles

Abstract: To explore the ordering mechanism of facet alloy nanocrystals with randomly distributed atoms, we investigate kinetic and thermodynamic behaviors of the ordering phase transition from face-centered cubic Pt3Co nanocrystals to L12-Pt3Co intermetallic nanocrystals. It is observed that the ordering occurs from the surface and then gradually into the interior in a layer-by-layer mode, involving the competition between two kinds of phase transition modes: long-range surface diffusion-induced phase transition (SDIPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…38 For instance, the phase transition of cubic Pt 3 Co nanocrystals from a solid solution to an intermetallic phase via high temperature annealing was investigated using in situ scanning transmission electron microscopy. 39 The results showed that two mechanisms of phase transition exist, resulting in a layer by layer ordering of atomic arrangements from the surface to interior. One is the long-range surface-diffusion-induced phase transition, which begins at relatively low temperature and could induce phase transition at the initial time at a temperature setting of 600 °C.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%
“…38 For instance, the phase transition of cubic Pt 3 Co nanocrystals from a solid solution to an intermetallic phase via high temperature annealing was investigated using in situ scanning transmission electron microscopy. 39 The results showed that two mechanisms of phase transition exist, resulting in a layer by layer ordering of atomic arrangements from the surface to interior. One is the long-range surface-diffusion-induced phase transition, which begins at relatively low temperature and could induce phase transition at the initial time at a temperature setting of 600 °C.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%
“…The interfaces generated from these defects commonly promote the catalytic activity by regulating the specific adsorption, desorption, and activation of molecules (39)(40)(41)(42)(43). To date, synthesis of intermetallic nanocrystals with controlled interface structure remains challenging, partially because of the complex growth and ordering processes (44)(45)(46)(47)(48)(49)(50). Regardless of the alluring performance, it is essential to elucidate the microscopic origin mechanisms of interface in intermetallic nanocrystals and its structure-function relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Although the surface-influenced ordering seems useful to control the Pt-Co nanoparticle structure, such ordering has not been observed. 5,19,20 Researchers have conducted annealing experiments of solid-solution particles. In those experiments, the particles had the ordered structure that can be expected from the total composition ratio and bulk phase diagram.…”
Section: Introductionmentioning
confidence: 99%